The Folkcommunication in times of Artificial Intelligence: Challenges, provocations and perspectives (Revista Internacional de Folkcomunicação, 2025)
Folkcommunication has stood out among the perspectives on popular informational mediations and also contemporary mediations. In times of profusion of artificial intelligence, how is this area, characterized as the first genuinely Brazilian theory of communication, impacted by these transformations? Due to its own epistemological issues and its origin and application among the marginalized, do artificial intelligences impact this communicational theory to a greater or lesser extent? These points are highlighted, analyzed and debated, taking as a case study reflecting the status of Folkcommunication in the middle of this third decade of the 21st century. It is emphasized that the theory proposed by Luiz Beltrão has been less impacted mainly by the perspectives of the guided groups themselves, even though there has been a modernization among its teachings, mainly because artificial intelligence deals with more quantitative and algorithmic perspectives, while Folkcommunication remains in its qualitative, affective and mediational perspectives, often involving audiences that are not even fully connected to the technological-internet and algorithmic times.